2011
DOI: 10.1111/j.1600-0870.2010.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

The Rossby Centre Regional Climate model RCA3: model description and performance

Abstract: A B S T R A C T This paper describes the third full release of the Rossby Centre Regional Climate model (RCA3), with an emphasis on changes compared to earlier versions, in particular the introduction of a new tiled land-surface scheme. The model performance over Europe when driven at the boundaries by ERA40 reanalysis is discussed and systematic biases identified. This discussion is performed for key near-surface variables, such as temperature, precipitation, wind speed and snow amounts at both seasonal and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
321
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 594 publications
(330 citation statements)
references
References 73 publications
6
321
0
3
Order By: Relevance
“…A thorough comparison of hindcast simulation results of the three biogeochemical models driven with regionalized ERA-40 re-analysis data (Samuelsson et al 2011(Samuelsson et al ) during 1970(Samuelsson et al -2005 was performed by Eilola et al (2011). Eilola et al (2011) concluded that the models capture much of the observed variability and that during 1970-2005, the response to changing physical conditions is simulated realistically.…”
Section: Baltic Sea Modelsmentioning
confidence: 99%
“…A thorough comparison of hindcast simulation results of the three biogeochemical models driven with regionalized ERA-40 re-analysis data (Samuelsson et al 2011(Samuelsson et al ) during 1970(Samuelsson et al -2005 was performed by Eilola et al (2011). Eilola et al (2011) concluded that the models capture much of the observed variability and that during 1970-2005, the response to changing physical conditions is simulated realistically.…”
Section: Baltic Sea Modelsmentioning
confidence: 99%
“…Bosshard et al (2014) considered all possible selections of two projections from this ensemble and noted that the chosen projections spanned a larger uncertainty range than at least 70 % of the other combinations. Both projections simulated effects of the A1B emission scenario (Nakićenović et al, 2000), and the GCM results were dynamically downscaled to 50 km using the regional climate model (RCM) called RCA3 (Samuelsson et al, 2011). Thereafter, daily surface temperatures (at 2 m) and precipitation were further downscaled to 4 km, and bias was corrected using the distribution-based scaling method (Yang et al, 2010) with reference data from the 4 km grid-based observations for 1981-2010.…”
Section: Model Approach To the Past And The Futurementioning
confidence: 99%
“…Lately, one can cite (Schimanke et al 2014) who used a EOF decomposition of atmospheric pressure over Northern Europe to identify the atmospheric patterns that create MBIs. Based on this decomposition and using five different climate scenarios (Samuelsson et al 2011), they have forecasted an increase of MBIs in the Baltic Sea towards the end of the 21st century. However, their study was only based on atmospheric patterns and did not include an ocean model.…”
Section: Introductionmentioning
confidence: 99%